Date Attachable Offline Electronic Cash Scheme - Chun-I Fan; Wei-Zhe Sun; Hoi-Tung Hau (The Scientific World Journal)
Electronic cash (e-cash) is definitely one of the most popular research topics in the e-commerce field. It is very important that e-cash be able to hold the anonymity and accuracy in order to preserve the privacy and rights of customers. There are two types of e-cash in general, which are online e-cash and offline e-cash. Both systems have their own pros and cons and they can be used to construct various applications. In this paper, we pioneer to propose a provably secure and efficient offline e-cash scheme with date attachability based on the blind signature technique, where expiration date and deposit date can be embedded in an e-cash simultaneously. With the help of expiration date, the bank can manage the huge database much more easily against unlimited growth, and the deposit date cannot be forged so that users are able to calculate the amount of interests they can receive in the future correctly. Furthermore, we offer security analysis and formal proofs for all essential properties of offline e-cash, which are anonymity control, unforgeability, conditional-traceability, and no-swindling.